Distributed coordination and environmental load distribution control for omni-directional vehicle - NAKAZAWA, Kazuo; USUKI, Yoshito (Kikai Gakkai ronbunshū = Transactions of the Japan Society of Mechanical Engineers, 2014)
As the demand for robots grows in society, the environments in which robots will be needed are becoming increasingly diversified. Robots will therefore have to possess high mobility so that they can maneuver safely and smoothly in these environments. One type of vehicle that is now attracting attention as a means of achieving such motion is the Omni Directional Vehicle (ODV). The ODV has great potential for use in a wide variety of fields including wheelchairs and transport robots, and the ODV has consequently been the subject of many studies. In past research, many types of special wheels and mechanisms have been devised and developed to achieve omnidirectional motion. The complicated structures of these special wheels, however, have generated problems in terms of durability and stability making it difficult to increase vehicle size and speed. In this paper, we consider application of omnidirectional motion to motorized wheelchairs and mobility scooters or to even vehicles larger in size, and we focus on a modular ODV that uses conventional wheels with a durable configuration and achieves omnidirectional motion by a simple mechanism. In this type of ODV, a wheel module is taken to be one unit, and we achieve omnidirectional motion through distributed coordination of multiple units. We also propose a technique for improving the efficiency of motor operation by distributing the environmental load generated by movement. To demonstrate the effectiveness of the proposed technique, we conducted simulations and an experiment with actual equipment using the developed OVD. The simulations were performed under a variety of conditions and showed that omnidirectional and efficient motion could be achieved by the proposed technique. The experiment with actual equipment examined the case of automatic driving and driving with a human on board and showed that the load applied to each wheel module by road conditions could be compensated for and that the load on motors could be minimized.